Building a bridge—an archeologist's perspective on the evolution of causal cognition - Haidle, Miriam N. (Frontiers in Psychology, 2014)
The cognitive capacities of fossil humans cannot be studied directly. Taking the evolution of causal cognition as an example this article demonstrates the use of bridging arguments from archaeological finds as starting point via identification/classification, behavioral reconstruc-tions, and cognitive interpretations to psychological models. Generally, tool use is linked to some causal understanding / agent construal as the tool broadens the subject’s specific capabil-ities by adding new characters to its action sphere. In human evolution, the distance between the primarily perceived problem and the solution satisfying this need increased markedly: from simple causal relations to effective chaining in secondary/modular tool use, and further to the use of composite tools, complementary tool sets and notional tools. This article describes the evolution of human tool behavior from the perspective of problem-solution-distance and dis-cusses the implications for a linked development of causal cognition.